Exploration Of Effective Anti-Urolithiatic Property Of Carissa Carandas L. Leaves Against Ethylene Glycol Induced Kidney Stones In Male Rats: Pharmaceutical Science-Pharmacology for Drug Discovery - Madathala Sreekanth; Veerasamy Hari Baskar; Nunna Bheema Lingeswara Prasad (International Journal of Life Science and Pharma Research, 2022)
Urolithiasis is a common disease that has been recognized and documented in medical literature even by the Greek and Roman physicians. Carissa carandas Linn., is ensconce all over India mostly in the semi-arid territory. Karonda trees are extensively cultured in the domicile gardens, farmer’s fields, and orchards as hedge-row plants. The aim of the research was to evaluate the antiurolithiatic property of Carissa carandas Linn. leaf extract in rats. Urolithiasis in male Wistar albino rats was experimentally induced by administration of 0.75% (v/v) ethylene glycol in drinking water ad libitum for 28 days. Also the animals were treated with three doses of EELCC (ethanolic extract of leaves of Carissa Carandas Linn.) i.e., 100, 200, 400 mg/kg and Cystone 750 mg/kg b.w., p.o., respectively once daily from 15th to 28th day. On the 29th day, the body-weight difference was measured and animals was housed in individual metabolic cages, urine (pooled) collected for 24 h. Blood was collected on the same day and centrifuged. Parameters like urinary volume and pH, urinary analysis (Calcium, Oxalate, Creatinine, Uric acid, Blood urea nitrogen, and Urea) and serum analysis (Calcium, Oxalate, Creatinine, Uric acid, Blood urea nitrogen, and Urea) were performed to access the antiurolithiatic activity. The urine was subjected to microscopical study to observe the CaOx crystals. Thereafter the animals were sacrificed, kidneys excised followed by weighing the difference and estimation of homogenate parameters (Calcium, Oxalate, MDA, GSH, Catalase and SOD). Histopathological study of the kidneys were done by light microscopy, whereas the EELCC treated rats (400 mg/kg) showed no presence of CaOx crystal deposits and apparently retained normal morphology, tubular epithelial cells and glomeruli as in normal control group when compared with Cystone (750 mg/kg). Urolithiasis caused significant (P< 0.01) changes in all parameters in lithiatic control group rats as compared to normal control group rats., treatment with EELCC at three doses i.e. 100, 200 and 400 mg/kg and Cystone 750 mg/kg showed comparatively a significant (P< 0.01) restoration of all altered parameters. Based on results it can be concluded that the EELCC at dose of 400 mg/kg exhibited significant (P< 0.01) anti-urolithiatic activity on experimentally induced urolithiasis.